The solvable subgroups of large order of L2(p) , pâ‰¥5 - Abduh, Abdullah A.; AlGhawazi, Abeer A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
By using the following theoretical and computational algorithms , we determined the solvable subgroups of large order of the finite non-abelian simple linear groups G = L2(p) = PSL(2,p) , for pâ‰¥5 and p is a prime number , also their presentations and permutation representations have been found .